Empowering Teachers' Professional Growth: Harnessing Smartphones for Collaboration, Self-monitoring, and Learning - Parajuli, Krishna Prasad (English Language Teaching Perspectives, 2024)
The growing use of smartphones in daily communications has emerged as a dynamic device in terms of storing information, searching online materials, and disseminating ideas. The technology has the potential to enhance teachers’ instructional activities. This study presents an analysis of secondary teachers' use of smartphones in their professional development. Twelve teachers were purposely selected to participate in this case study. The data collected through the semi-structured interviews and participant observation were thematically analysed. The study found that although teachers were not compelled to use digital technology in their professional activities, they used smartphones to update their professional knowledge and skills, monitor their performance, and seek support from other teachers by networking and collaborating . The findings indicate that the use of smartphones in instructional activities did not transform their traditional pedagogies. However, teachers harnessed their smartphones as educational technology for professional development, particularly in learning subject matter and monitoring self performance and problem solving by networking and collaborating with teachers because of the perceived usefulness and ease of use of the technology. Researchers, teacher trainers, teachers, and policymakers need to reconsider the benefits of the educational use of smartphones in teachers' professional development as has given its presence in the personal and professional lives of teachers.